Kualitas relasi dan resiliensi orang tua anak dengan disabilitas intelektual - Amalia Senja; Soewadi Soewadi; Intansari Nurjannah (Berita Kedokteran Masyarakat (BKM), 2017)
The quality of parent-children relationship and resilience among parents with children with intellectual disabilityPurposehis study was conducted to know the relation between quality of parent-child relationship and resilience among parents of children with intellectual disability.MethodsThis cross-sectional study was conducted from June - July 2015 at SLB N 1 Bantul Yogyakarta city while the instrument test was conducted on 20 parents who had children with intellectual disability in SLB Darma Bhakti Piyungan, Yogyakarta. The population in this study were all parents with children with intellectual disability in SLB N 1 Bantul from TKLB level to SMALB. The samples were 60 respondents.ResultsThis study found no association between the quality of parent-child relationships with parental resilience with intellectual disability children. ConclusionThe authors suggest that resilience variables are not directly linked to the variable quality of relations but there are also other variables that influence it such as social support and others.